2019
DOI: 10.1111/jace.16443
|View full text |Cite
|
Sign up to set email alerts
|

0D CoP cocatalyst/ 2D g‐C3N4 nanosheets: An efficient photocatalyst for promoting photocatalytic hydrogen evolution

Abstract: In this work, cobalt phosphide (CoP) nanoparticles were successfully decorated on an ultrathin g‐C3N4 nanosheet photocatalysts by in situ chemical deposition. The built‐in electric field formed by heterojunction interface of the CoP/g‐C3N4 composite semiconductor can accelerate the transmission and separation of photogenerated charge‐hole pairs and effectively improve the photocatalytic performance. TEM, HRTEM, XPS, and SPV analysis showed that CoP/g‐C3N4 formed a stable heterogeneous interface and effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…The ESR spectra with DMPO as the trapping agent were acquired for CN-ThA30 and g-C3N4 ( Fig. 9(b)), indicating the existence of •O2  and •OH under light excitation [69,70]. No Combined with the experimental results of hydroxyl group capture by IPA, the formation of •OH radicals enhances the photocatalytic activity.…”
Section: Mechanism Of Photocatalytic Activity Enhancementmentioning
confidence: 77%
“…The ESR spectra with DMPO as the trapping agent were acquired for CN-ThA30 and g-C3N4 ( Fig. 9(b)), indicating the existence of •O2  and •OH under light excitation [69,70]. No Combined with the experimental results of hydroxyl group capture by IPA, the formation of •OH radicals enhances the photocatalytic activity.…”
Section: Mechanism Of Photocatalytic Activity Enhancementmentioning
confidence: 77%
“…SPV spectroscopy is a powerful tool for investigating the charge separation efficiency in the semiconductor materials [32]. SPV technology is an excellent way to study the photoinduced charge behavior at the interface of semiconductors, which obtain relevant information by analyzing the change of the surface voltage of the material [33]. It is known that SPV signal intensity is sensitive to the charge separation efficiency [34].…”
Section: Photocatalytic Performance Of Wo 3 /G-c 3 N 4 Composite Withmentioning
confidence: 99%
“…In this regard, transition-metal phosphides (TMPs), such as CoP [32], Co2P [33], MoP [34], and Cu3P [35] have higher potential as electrocatalysts due to their low cost, outstanding catalytic activity, and stability for the HER [36,37]. Researchers have confirmed that the above electrocatalysts can effectively enhance the photocatalytic HER activity as co-catalysts [38][39][40][41][42]. Consequently, we believe that this strategy for finding photocatalytic co-catalysts from TMPs is feasible.…”
Section: Introductionmentioning
confidence: 99%